INFLUENCE OF SERVICE QUALITY ON SWITCHING BEHAVIOR MEDIATED BY RELATIONSHIP QUALITY IN SPRING BED RETAILERS IN JABODETABEK - Djong Hermanto (Universitas Trisakti, 2010)
Retailers in the spring bed business have a privilege to choose among the various products offered by various suppliers. Typically, these retailers would have chosen the suppliers whose products are matched with their needs and at the same time could give higher profits. This condition has strengthened the competition in the spring bed industry. In order to face the challenges that come from the retailers’ switching behavior, every supplier has to give a good service quality and build a strong relationship quality with their retailers. In this study, relationship quality was measured by three components: satisfaction, trust and commitment from the retailers to the suppliers.The objective of the study is to analyze the impact of service quality on switching behavior which was mediated by the relationship quality. The components of relationship quality are: satisfaction, trust and commitment. A theoretical framework was developed as the hypotheses for testing the impact of every variables were constructed. The samples of this study were 341 spring bed retailers in Jabodetabek (Jakarta, Bogor, Depok, Tangerang and Bekasi) area. A sixpoint Likert-type scale was used for the questionnaire variables, with 1 = strongly disagree and 6 = strongly agree. The quantitative analysis with Structural Equation Modelling (SEM) was completed using Lisrel 8.8. The structural model of this study could explain the interrelationship among each variables in the model. As a result, from ten hypotheses there were five findings supporting the hypotheses: service quality had an impact on satisfaction, service quality had an impact on trust, satisfaction had an impact on trust, trust had an impact on commitment, and commitment had an impact on commitment. The findings which did not support the hypotheseswere: There was no impact of service quality on commitment and switching behavior; there is no impact of satisfaction on commitment and switching behavior; and finally there is no impact of trust on switching behavior. As a conclusion, the result of the study described the importance of service quality in manufactured industry, in the business to business context between spring bed suppliers and retailers. The impact of service quality on the switching behavior was mediated by relationship quality, where commitment was the important component of relationship quality that greatly affecting the strength of service quality impact on switching behavior. For future studies, researchers may explored other model to investigate more variables with more proper indicators, more homogeneous samples and longer period of research